Technopreneurship : Digital Marketing In The Development of The Creative Culinary Industry in Makassar City - S, Muh Rizal; Siraj, Muhammad Luthfi; Syarifuddin, Syarifuddin; Agriyanto, Dody; Ismail, Ismaniar (Universitas Negeri Makassar, 2024)
The development of the culinary industry world that is increasing without realizing it also provides an increase in public interest that is understood in the business world, the integration of technology and understanding of its use can be a weapon for business actors to be one step ahead compared to their competitors or also called competitive advantage. Digital marketing is one of the media that is often used by business actors because of the new ability of consumers to follow the flow of digitalization, several companies are gradually starting to abandon the conventional marketing model / and switch to modern marketing. This research is a descriptive qualitative type with a phenomenological research approach to describe all phenomena of how the digital marketing literacy model in the development of the creative culinary home industry in the city of Makassar. The aspects that are the focus of this researchsocial networking, transliteracy, maintaining privacy, managing identity, creating content. The type of data source in this study used primary and secondary data with observation and interview data collection techniques. The data analysis technique used qualitative descriptive analysis. The results of the research findings are known Digital marketing model in the development of the culinary creative industry in the tourist alley of Makassar city is carried out through three stages, namely 1) Data Based and Use of Big Data and Analytics, 2) Optimization of Digital-Based Business Incubators, and 3) Creation of Educational and Interactive Content and Location-Based Marketing (Geo-Targeting).Strategies that the government can apply to culinary industry players in Makassar in utilizing platforms for culinary developmentwith four stages, namely the Development of MSMEs Based on Collaboration of Actors in Creating a One-Stop Database, Human Resource Development Through Continuous Optimization of Training for Business Actors, Providing an E-Commerce Platform Model for Business Actors, and Building Brand Awareness